Fertilization turns a rubber plantation from sink to methane source - D. Epron; D. Epron; R. Chotiphan; Z. Wang; O. Duangngam; M. Shibata; S. K. Paul; T. Mochidome; J. Sathornkich; W. A. Azuma; J. Murase; J. Murase; et al. (Biogeosciences)
The rapid expansion of rubber cultivation, driven by the demand for natural rubber in the tire industry, constitutes a significant land-use change in Southeast Asia. This significant land-use change has reduced soil methane (CH4) uptake, thereby weakening atmospheric CH4 removal over extensive areas. While fertilization is a widespread practice in rubber plantations, its role in further weakening the soil CH4 sink has remained poorly understood. Over 1.5 years, we measured soil CH4 fluxes biweekly (every 2 weeks) in an experimental rubber plantation with four distinct fertilization treatments to evaluate their impact on the soil CH4 uptake. Our findings revealed that fertilization not only reduced soil CH4 consumption, but also increased soil CH4 production. The difference in soil CH4 uptake between unfertilized plots (−2.9 kg CH4 ha−1 yr−1) and those with rational fertilization (−2.1 kg CH4 ha−1 yr−1) was moderate. Recommended fertilization rates reduced soil CH4 uptake by 60 % (−1.1 kg CH4 ha−1 yr−1), and heavy fertilization transformed the soil into a net source of CH4 (+0.3 kg CH4 ha−1 yr−1). The suppression of soil CH4 oxidation was likely driven by increased mineral nitrogen in the soil solution and soil acidification, while elevated dissolved organic carbon likely stimulated CH4 production in the topsoil. Most rubber tree trunks emitted CH4, likely of internal origin. Trunk CH4 fluxes ranged from −0.10 to 0.51 nmol s−1 per tree, with no significant fertilization effect. At the national level, adopting rational fertilization practices in Thailand could enhance the net soil CH4 sink by 5.9 Gg CH4 yr−1. However, this mitigation strategy would have a limited impact on the overall greenhouse gas budget of the agricultural sector in Southeast Asia, unless it is extended to other tree plantations and cropping systems.